Physical activity and glioblastoma: a paradigm shift in neuro-oncology therapy - Xie, Lin; Wang, Feng (Frontiers in Oncology, 2025)
Glioblastoma (GBM) is a highly aggressive brain tumor with a poor prognosis, characterized by rapid progression and limited treatment options. This review explores the emerging role of physical activity as a complementary therapy in GBM management, focusing on its multifaceted effects on tumor biology, immune modulation, and patient quality of life. Exercise has been shown to influence key molecular pathways involved in GBM progression, including the RTK/PI3K/Akt/mTOR signaling cascade, angiogenesis, and metabolic reprogramming. Additionally, physical activity enhances immune surveillance by mobilizing cytotoxic T cells and natural killer (NK) cells, while reducing immunosuppressive cells like Tregs and MDSCs. Clinical and preclinical evidence suggests that exercise may improve cognitive function, reduce treatment-related toxicity, and prolong survival in GBM patients. Despite these promising findings, significant gaps remain in understanding the optimal exercise regimens and their mechanistic underpinnings. Future research should prioritize personalized approaches, integration with novel therapies, and multi-omics analyses to elucidate exercise-induced changes in the tumor microenvironment (TME). This review underscores the potential of physical activity to revolutionize neuro-oncology therapy, offering a paradigm shift in GBM treatment strategies.